1992
DOI: 10.1111/j.1349-7006.1992.tb02723.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered Glycosylation of Membrane Glycoproteins Associated with Human Mammary Carcinoma

Abstract: N‐Linked sugar chains of normal mammary gland, mammary carcinomas (primary lesion), and axillary lymph node metastases of mammary carcinomas were released from their membrane preparations by hydrazinolysis and their structures were analyzed. Fractionation using a Datura stramonium agglutinin (DSA)‐Sepharose column revealed that the metastasized carcinomas contain more than twice as much DSA‐binding oligosaccharides as the normal gland, and the primary carcinomas contain an intermediate amount. These oligosacch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
2

Year Published

1995
1995
2004
2004

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 31 publications
0
27
2
Order By: Relevance
“…Detailed structural studies of N-glycans isolated from baby hamster kidney cells and polyoma-or Rous sarcoma virustransformed baby hamster kidney cells showed that the increase in the GlcNAc␤136 branch attached to the Man␣136Man arm of the trimannosyl cores is the structural basis for this phenomenon (5,6). This was further confirmed by studies on a number of malignant cell lines transformed with different agents (7)(8)(9).…”
Section: Takeshi Sato ‡ and Kiyoshi Furukawamentioning
confidence: 63%
See 1 more Smart Citation
“…Detailed structural studies of N-glycans isolated from baby hamster kidney cells and polyoma-or Rous sarcoma virustransformed baby hamster kidney cells showed that the increase in the GlcNAc␤136 branch attached to the Man␣136Man arm of the trimannosyl cores is the structural basis for this phenomenon (5,6). This was further confirmed by studies on a number of malignant cell lines transformed with different agents (7)(8)(9).…”
Section: Takeshi Sato ‡ and Kiyoshi Furukawamentioning
confidence: 63%
“…Structural analysis of the N-glycans of these cells revealed that only about 20% of the glycoproteins from 3T3 and MT1 cells have highly branched N-glycans with the Gal␤134GlcNAc␤136(Gal␤134GlcNAc␤132)Man branch compared with 31 and 39% of the glycoproteins from MTPy and MTAg cells, respectively, indicating a proportionality between increased highly branched N-glycans and tumorigenic and metastatic potentials (11). The increased expression of the highly branched N-glycans also correlates with the tumor forming activities of various other transformed cells (7,9). The increased cell surface binding of fluorescein-labeled leukophytohemagglutinin (L-PHA), 1 which specifically binds to highly branched N-glycans with the Gal␤134GlcNAc␤136-(Gal␤134GlcNAc␤132)Man branch (12), was found to correlate with the metastatic potentials of mouse mammary carcinoma cells, mouse lymphoma cells, transformed rat fibroblasts, and human breast cancers (13,14).…”
Section: Takeshi Sato ‡ and Kiyoshi Furukawamentioning
confidence: 99%
“…These glycoproteins are found to be localized in lysosomes, Golgi apparatus, and cytoplasm of HeLa or MCF-7 cells. DSA lectin, which specifically recognizes [31-6 branched oligosaccharides, reacts with breast carcinomas in a pattern similar to that of anti-h-lamp-1 and h-lamp-2 antibodies [17]. Dennis and colleagues also purified two similar glycoproteins, termed P2A (110 kD) and P2B (130 kD), from highly metastatic murine lymphoid tumor cells, MDAY-D2 [48].…”
Section: Discussionmentioning
confidence: 96%
“…Several evidences have been reported that 131-6 branched oligosaccharides are expressed in human breast [12,17], colon [12], or esophageal [19,21] carcinomas. However, molecular characteristics of the glycoproteins bearing [31-6 branched oligosaccharides in human breast carcinoma still remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation